The next generation of physician-researchers: undergraduate medical students’ and residents’ attitudes, challenges, and approaches towards addressing them - Behnaz Mokhtari; Reza Badalzadeh; Saeideh Ghaffarifar (BMC Medical Education)
Abstract Background Undergraduate medical education and residency training are critical periods for conducting research. Medical diagnoses and therapies are direct results of successful research efforts that have advanced several scientific fields. This review highlights the importance of incorporating scientific research training into the curricula of undergraduate medical education and residency programs. Methods We utilized key databases such as PubMed, Web of Science, and Google Scholar to conduct a narrative review of English-language articles published between 2002 and 2024. Ultimately, we selected 49 studies that examined the attitudes of undergraduate medical students and residents toward research, the common challenges they encounter while participating in research activities, and the strategies that support and encourage their involvement, all in alignment with our study objectives and keywords. In addition, we identified several relevant themes, including the value of research experience in shaping well-rounded medical professionals; the integrity of research practices in residency selection, which addresses concerns such as the arms race and misrepresentation, as well as the balance between quality and quantity; striking a balance between research and clinical training while promoting equity and inclusion; and effective programs and mentorship strategies to enhance research engagement. Results Translating the positive attitudes of undergraduate medical students and residents into improved knowledge and practice necessitates the development of structured mentoring programs and advanced training systems. Institutions must provide the necessary tools, guidance, and support to overcome research barriers. This will help establish an environment in undergraduate medical education and residency training that values research, facilitates access to it, and integrates it into the curriculum. Conclusions To address the critical shortage of physician-researchers and improve evidence-based medical practice, it is crucial for medical schools to focus on research education and create avenues for student involvement. By tackling research challenges and implementing supportive strategies, these efforts empower the next generation of physician-researchers to embrace research, contribute to medical progress, and uphold the highest standards of patient care.